Back Cover: Solid‐State Phosphorescence of trans‐Bis(salicylaldiminato)platinum(II) Complexes Bearing Long Alkyl Chains: Morphology Control towards Intense Emission (Chem. Eur. J. 29/2013). Issue 29 (8th July 2013) - Komiya, Naruyoshi; Itami, Nao; Naota, Takeshi
<x xml:space="preserve">Abstract</x> Morphology control of trans‐bis(salicylaldiminato)PtII complexes bearing long alkyl chains can change typically non‐emissive crystals into highly emissive crystals. Crystals prepared using "kinetic" conditions, including rapid cooling, high concentrations and poor solvents, emit intense yellow phosphorescence under UV illumination at an ambient temperature, whereas crystals prepared using ordinary thermodynamic conditions were non‐ or less emissive. Powder and single‐crystal XRD analysis of various crystalline polymorphs revealed that crystal engineering from a typical stacking molecular array to face‐to‐edge packing motif is a key for the OFF–ON control of solid‐state emission. For more details, see the Full Paper by T. Naota et al. on page 9497 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>